Pharmacokinetic Analysis of Weekly Versus Biweekly IgPro20 Dosing in Patients With Primary Immunodeficiency. Issue 6 (8th December 2019) - Rojavin, Mikhail A.; Chapdelaine, Hugo; Tortorici, Michael A.; Praus, Michaela; Baheti, Gautam; Zhang, Ying; Hofmann, Jutta; Labrosse, Roxane; Dicaire, Renée; Haddad, Elie
Abstract: Flexible dosing of IgPro20 (Hizentra®, CSL Behring, King of Prussia, Pennsylvania) maintains normal serum immunoglobulin G (IgG) levels in patients with primary immunodeficiencies (PID). Until now, clinical trials testing the pharmacokinetic (PK) characteristics of serum IgG of weekly and biweekly subcutaneous IgG therapy were not published. This is the first study assessing PK characteristics following weekly and biweekly IgPro20 in patients with PID. The PK study was conducted in 2 parts: weekly dosing (12 weeks) and biweekly dosing (up to 12 months). Serum IgG concentration‐time data were analyzed using noncompartmental methods to generate PK parameters. Fifteen patients provided PK samples for both dosing regimens. For weekly and biweekly regimens, mean doses per infusion were 109 and 213 mg/kg, respectively, and median tmax was 2.0 and 3.02 days, respectively. The mean Ctrough values were similar in weekly and biweekly regimens (10.21 and 10.13 g/dL, respectively). The geometric mean ratios (GMRs) with 90% confidence intervals of biweekly to weekly Cmax and Ctrough were 1.10 (1.06–1.13) and 0.98 (0.95–1.01), respectively. The GMR of dAUC was 1.07 (1.03–1.10). This PK analysis demonstrated similar systemic IgG exposure after weekly and biweekly IgPro20 dosing with an equivalent monthly dose in patients with PID.